Blasphemy, Islam and the state: pluralism and liberalism in Indonesia - Fenwick, Stewart (ICLARS series on law and religion, 2017)
Islam and pluralism -- Rawls and the challenge of faith -- Faith and freedom in Indonesian law -- MUI : the institutionalising of Indonesian islam -- Case study part 1 : the language of devotion -- Case study part 2 : innovation on trial -- Islam, public reason and the state